Aceruloplasminemia. Issue 1 (28th August 2014) - Miyajima, Hiroaki
<x xml:space="preserve">Abstract</x> Aceruloplasminemia is characterized by progressive neurodegeneration with brain iron accumulation due to the complete lack of ceruloplasmin ferroxidase activity caused by mutations in the ceruloplasmin gene. Redox‐active iron accumulation was found to be more prominent in the astrocytes than in the neurons. The most characteristic findings were abnormal or deformed astrocytes and globular structures of astrocytes. The lack of ceruloplasmin may primarily damage astrocytes in the aceruloplasminemic brains as a result of lipid peroxidation due to massive iron deposition. In the normal brain, iron may be continuously recycled between astrocytes and neurons, with transferrin acting as a shuttle. The glycosylphosphatidylinositol (GPI)‐linked ceruloplasmin on astrocytes functions as a ferroxidase, mediating the oxidation of ferrous iron transported from the cytosol by ferroportin and its subsequent transfer to transferrin. In cases with aceruloplasminemia, neurons take up the iron from alternative sources of non‐transferrin‐bound iron, because astrocytes without GPI‐linked ceruloplasmin cannot transport iron to transferrin. The excess iron in astrocytes could result in oxidative damage to these cells, and the neuronal cell protection offered by astrocytes would thus be disrupted. Neuronal cell loss may result from iron starvation in the early stage and from iron‐mediated oxidation in the late stage. Ceruloplasmin may therefore play an essential role in neuronal survival in the central nervous system.